Speak-to-Write from Multiple Perspectives, as Method - Eidsheim, Nina Sun; Bellocq, Juliette (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
One of the practice-based research methods that excites me the most today is to work with writing as a practice, and as a practice-based research method. The technology of writing can be very misleading, especially when that writing is typed using a word processing program. When using this tool, writing looks the same whether it represents a stream of consciousness, a first draft, or a final proof. Because of this, I have found that I hold myself to the standard of the final version, which of course completely freezes me up. If we are always aiming for the final version, there is not much room for thinking, making errors, going sideways and backward and forward again. There is only the guaranteed feeling of failure.In response, graphic designer Juliette Bellocq and I have developed a set of writing exercises that address these two limitations, as I have come to know writing from my training as an academic. In this piece, we share our exercise, 1,000 Ways Home. It is a non-linear process of thinking and writing. It also offers the alchemy of communicating in the presence of another person who pays close attention. We call our process speak-to-write.